2017
DOI: 10.1038/mp.2017.90
|View full text |Cite
|
Sign up to set email alerts
|

Exocytosis-related genes and response to methylphenidate treatment in adults with ADHD

Abstract: Experimental studies have demonstrated that methylphenidate (MPH) modulates the synaptic vesicle trafficking and synaptotagmin-1 (SytI) mRNA levels. SytI is a regulatory protein of the SNARE complex, a neurotransmitter exocytosis mediator. Despite this evidence, most SNARE complex-related genes have never been evaluated in attention-deficit/hyperactivity disorder (ADHD) pharmacogenetics. This study evaluates, for we believe the first time, polymorphisms on the SNARE complex-related genes STX1A (rs2228607), VAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
11
0
1
Order By: Relevance
“…Since therapy is mainly based on improvement of dopaminergic neurotransmission, it is plausible to expect a stronger effect of genes involved in the mediation of dopaminergic effects. Smaller studies have shown that polymorphisms in genes of catecholaminergic neurotransmission [66] or the SNARE complex of the synapse can indeed predict the response to stimulant therapy [67].…”
Section: Discussionmentioning
confidence: 99%
“…Since therapy is mainly based on improvement of dopaminergic neurotransmission, it is plausible to expect a stronger effect of genes involved in the mediation of dopaminergic effects. Smaller studies have shown that polymorphisms in genes of catecholaminergic neurotransmission [66] or the SNARE complex of the synapse can indeed predict the response to stimulant therapy [67].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the treatment response of methylphenidate was suggested to rely on inter-individual variability in the amount of dopamine released by neurons (Volkow et al, 2002; Berridge et al, 2006; Hannestad et al, 2010). Certain polymorphisms, such as the 40-pb variable number tandem repeat polymorphism, noradrenaline, and serotonin transporter genes, were also suggested to be associated with the treatment response to methylphenidate (Winsberg and Comings, 1999; Yang et al, 2004; Thakur et al, 2010; Froehlich et al, 2011b; Bidwell et al, 2017; da Silva et al, 2018). However, recent meta-analyses did not support this polymorphism association hypothesis (Kambeitz et al, 2014; Bonvicini et al, 2016).…”
Section: Heterogeneity Of Clinical Profiles Of Adhdmentioning
confidence: 99%
“…The latter argument, in particular, suggests that scientists’ methods are currently no better than a random selection of genes when it comes to putting together plausible biologically motivated gene sets . While such candidate‐driven association studies have generated initial promising results and applications (e.g., in the pharmacogenomics of methylphenidate treatment), most recent studies have concentrated on whole‐genome genotyping.…”
Section: Molecular Genetic Studiesmentioning
confidence: 99%